Ir56b is an atypical ionotropic receptor that underlies appetitive salt response in Drosophila. - Dweck, H.K.M.; Talross, G.J.S.; Luo, Y.; Ebrahim, S.A.M.; Carlson, J.R. (Current Biology, 2022)
Salt taste is one of the most ancient of all sensory modalities. However, the molecular basis of salt taste remains unclear in invertebrates. Here, we show that the response to low, appetitive salt concentrations in Drosophila depends on Ir56b, an atypical member of the ionotropic receptor (Ir) family. Ir56b acts in concert with two coreceptors, Ir25a and Ir76b. Mutation of Ir56b virtually eliminates an appetitive behavioral response to salt. Ir56b is expressed in neurons that also sense sugars via members of the Gr (gustatory receptor) family. Misexpression of Ir56b in bitter-sensing neurons confers physiological responses to appetitive doses of salt. Ir56b is unique among tuning Irs in containing virtually no N-terminal region, a feature that is evolutionarily conserved. Moreover, Ir56b is a "pseudo-pseudogene": its coding sequence contains a premature stop codon that can be replaced with a sense codon without loss of function. This stop codon is conserved among many Drosophila species but is absent in a number of species associated with cactus in arid regions. Thus, Ir56b serves the evolutionarily ancient function of salt detection in neurons that underlie both salt and sweet taste modalities.